Draft Annual Plan (2001-2002) Government of Arunachal Pradesh - Planning Commission (Planning Commission, 2001)
Arunachal Pradesh is situated in the North Eastern part of India. It borders the plains of Brahmaputra and gradually rises up in hills towards Himalayas and reaches over to 7,300 metres at Gorichen in West Kameng District. It has international border with Bhutan in the west. China in North and North-East and Myanmar in the East. the total length of international border is about 1628 Kms. It has inter-state borders with Nagaland in East and South- East and Assam in the South.
Department of Planning, Government of Arunachal Pradesh